Exploring Teachers' Corrective Feedback on EFL Speaking Performance : Narrative Study of Indonesian Private University - Khasanah, Maulidatul; Mahbub, Moh. Arif; Al Fauzi, Fatih (Linguapedia, 2024)
An abundant of literatures on oral corrective feedback has been burgeoning in distintive focuse area in various countries around the world. however, the study that involve narrative analysis study in Indonesian university level in speaking program is tend to still infinited. This current study purposed to exploring teachers’ oral corrective feedback on EFL speaking performance at islamic private university in East Java, Indonesia. By adapting Gulnaz (2019) interview frameworks which consist of four target discussion included are teachers’ beliefs, practices, effectiveness perceptions, and types of oral corrective feedback (OCF) applied in the classroom speaking activites. This narrative qualitative methods (Connelly & Clandinin, 1990) employed semi-structured interviews as the intruments. A face-to-face interview consisting 4 items directed to 1 partisipants who lisenced to take part in this study. To analyze the qualitative data, thematic analysis proposed by widodo (2014) was applied sytematically. The findings indicated that there were a lot of teachers’ preferences to practiced OCF using several types of explicit correction so that it was effective for their students’ speaking skills for the future.